Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik pada UMKM di Kabupaten Manokwari - Ika Puji Ladesthi Mahartuti; Syarifuddin Syarifuddin; Mona Permatasari Mokodompit (Akuntabilitas, 2020)
The Financial Accounting Standard Board has made Financial Accounting Standards for Entities without Public Accountability (SAK ETAP) to facilitate Micro, Small and Medium Enterprises (MSMEs) actors in presenting accounting information, but in fact the implementation of SAK ETAP is still low. The aim of this study is to anaylze the factors that influence the implementation of SAK ETAP in MSMEs in Manokwari Regency. Data research was obtained through questionnaires given to 81 MSMEs’ trade sector owners in Manokwari Regency. Data wereanalyzed using multiple linear regression analysis. The results showed that only qualitative financial statement characeristic factor that have significant influence on the implementation of SAK ETAP in MSMEs in Manokwari Regency. Whereas the factors of providing information and socialization, understanding of information technology, business size, length of business and owner’s educational background have no significant influence on the implementation of SAK ETAP in MSMEs in Manokwari Regency